Enhancing Voter Awareness Through Election Law Socialisation in Limo Village (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
General elections (elections) are the main pillars of democracy that demand active public participation, transparency, and integrity. Amendments to the Election Law and the Constitutional Court Decision No. 135/PUU-XXII/2024 have important implications for the national and regional simultaneous election systems. However, low political literacy, apathy, money politics, and hoaxes are still challenges. This study addresses the following questions: (1) the extent of the understanding of the people of Limo Village regarding changes in election regulations, and (2) the effectiveness of socialisation in increasing the awareness of socialisation participants about voting rights in general elections and active voter participation. The method used in this community service is Participatory Action Research (PAR), with 18 socialisation participants as the subjects, using discussion forums, election simulations, and questionnaire evaluations. The study found an increase in residents' understanding: previously, 16 people were unaware of the change in general election rules, and this understanding rose to 100% (a 100% increase). In addition, this socialisation also resulted in an understanding level of 83.3% (15 out of 18 participants) on citizens' voting rights due to changes in general election regulations. This socialisation also contributes to the Sustainable Development Goals (SDGs), especially quality education (SDG 4), gender equality (SDG 5), Reduced Inequalities (SDG 10), Peace, Justice, and Strong Institutions (SDG 16) 16, and Partnerships for the Goals (SDG 17).